Long Non-coding RNA in Neuronal Development and Neurological Disorders - Li, Ling; Zhuang, Yingliang; Zhao, Xingsen; Li, Xuekun (Frontiers in Genetics, 2019)
Long non-coding RNAs (lncRNAs) are transcripts which are usually more than 200nt at length, and do not have the protein-coding capacity. LncRNAs can be categorized based on their generation from distinct DNA elements, or derived from specific RNA processing pathways. During the past several decades, dramatic progresses have been made in understanding the regulatory functions of lncRNAs in diverse biological processes including RNA processing and editing, cell fate determination, dosage compensation, genomic imprinting and development, etc. Dysregulation of lncRNAs involves in multiple human diseases, especially neurological disorders. In this review, we summarized the recent progress about the function of lncRNAs and associated molecular mechanisms with a focus on neuronal development and neurological disorders.